Therapeutic Perspectives of 8-Prenylnaringenin, a Potent Phytoestrogen from Hops - Štulíková, Kateřina; Karabín, Marcel; Nešpor, Jakub; Dostálek, Pavel (Molecules (Basel, Switzerland), 2018)
Hop (Humulus lupulus L.), as a key ingredient for beer brewing, is also a source of many biologically active molecules. A notable compound, 8-prenylnaringenin (8-PN), structurally belonging to the group of prenylated flavonoids, was shown to be a potent phytoestrogen, and thus, became the topic of active research. Here, we overview the pharmacological properties of 8-PN and its therapeutic opportunities. Due to its estrogenic effects, administration of 8-PN represents a novel therapeutic approach to the treatment of menopausal and post-menopausal symptoms that occur as a consequence of a progressive decline in hormone levels in women. Application of 8-PN in the treatment of menopause has been clinically examined with promising results. Other activities that have already been assessed include the potential to prevent bone-resorption or inhibition of tumor growth. On the other hand, the use of phytoestrogens is frequently questioned regarding possible adverse effects associated with long-term consumption. In conclusion, we emphasize the implications of using 8-PN in future treatments of menopausal and post-menopausal symptoms, including the need for precise evidence and further investigations to define the safety risks related to its therapeutic use.
Keywords: Osteoporosis, Postmenopausal; hops; Antineoplastic Agents, Phytogenic; 8-prenylnaringenin; molekulární struktura; Molecular Structure; phytoestrogens; Menopause; menopause; postmenopauzální osteoporóza; menopauza; Flavanones; lidé; ženské pohlaví; Humans; Humulus; fytogenní protinádorové látky; fytoestrogeny; Female; flavanony; Phytoestrogens